INTEGRATION OF CUSTOMARY LAW AND CONFLICT RESOLUTION IN MULTICULTURAL SOCIETIES - Dewi, Mieke Anggraeni; Kuswarini, Kuswarini; Winarni, Widiati Dwi (Universitas 17 Agustus 1945 Semarang, 2025)
The purpose of this research is to analyze the challenges in integrating customary law into Indonesia's national legal system and to identify mechanisms for resolving customary law conflicts. The methodology used is a normative legal research with an empirical and legislative approach, where the data collected comes from literature review and legal studies. These data are qualitatively analyzed to understand the relationship between customary law and state law, as well as the challenges faced in their integration process. The findings show that one of the main challenges in integrating customary law into national law is the difficulty in harmonizing the local wisdom values embedded in customary law with the more formal and universal state legal system. The normative discrepancies between the two often lead to legal conflicts, especially in communities that have a legal system deeply intertwined with local culture and social structure. Additionally, the limited knowledge of customary law among indigenous peoples and law enforcement officers also hampers the effective implementation of state law. A successful integration process requires an inclusive approach involving the government, indigenous communities, and other stakeholders in creating dispute resolution mechanisms based on mediation and cross-cultural dialogue. The conclusion of this study is that the integration of customary law into the national legal system requires strategic measures that respect local wisdom values, strengthen the capacity of indigenous communities in understanding law, and support policies that encourage conflict resolution through dialogue and mediation. The recommendation proposed is the importance of formulating policies that provide space for customary law within the national legal framework, as well as the need for training law enforcement officers on customary law to ensure a harmonious and mutually supportive integration of both legal systems.